Estimating determinant of innovations by generalized methods of moments with persistence of panel data on developing countries - Nurnaddia Nordin; NurHaiza Nordin; Norzalina Zainudin (2016)
This paper addresses the empirical analysis of determinant of innovations in developing countries by using Generalized Methods of Moments (GMM) estimating on panel data that consists of 52 countries. Innovation defined as a process that attempt to try out new or improved products, processes or ways to do. In order to achieve this phase, past studies address a few determinants of innovations such as human capital, patent, trademark, regulation, stock market and trade openness. This paper analyses the question: which factor will contribute to successful innovation? By using GMM method, we estimate the data at the difference and system GMM with one-step and two steps. The results addresses that trade openness are highly significant in determine innovation in developing countries. Thus our finding provides that free trade is the most important determinant to encourage innovation activities in developing countries.